A systematic review and meta-analysis on the epidemiology of work-related musculoskeletal disorders among nurses in Ethiopia - Abel Desalegn Demeke; Abraham Dessie Gessesse; Etaferaw Bekele Auddo; Takla Tamir; Alem Bayable; Ababo Demeke (PLoS ONE, 2026)
Background Work-related musculoskeletal disorders (WMSDs) are among the most prevalent work-related disorders affecting individuals across all age groups and professions. Nurses are highly vulnerable due to the nature of their professional duties. However, no comprehensive meta-analysis has been done on the prevalence of WMSDs among nurses. Thus, the purpose of this study was to provide the pooled prevalence and associated factors of WMSDs among nurses in Ethiopia. Methods This review was registered with PROSPERO (CRD420251136383). To retrieve relevant studies, various electronic databases such as PubMed, Science Direct, HINARI, and Google Scholar were searched from inception to August 14, 2025. The Joana Briggs Institute critical appraisal tool was used for literature quality assessment. The necessary data were extracted and analyzed with STATA 17. A random-effects model was employed to estimate the pooled prevalence of WMSDs and associated factors while also evaluating heterogeneity and publication bias. Furthermore, a nonparametric trim and fill analysis and leave-one-out sensitivity analysis were conducted. Results A total of sixteen studies containing 5982 nurses were included in this study. The pooled prevalence of WMSDs among nurses in Ethiopia was 61.47% (95% CI: 55.08–67.87). Being female (PAOR = 1.37; 95% CI: 1.08–1.75), job stress (PAOR = 1.85; 95% CI: 1.34–2.56), prolonged standing (PAOR = 1.85; 95% CI: 1.29–2.66), and work experience (≥ 5 years) (PAOR = 1.58; 95% CI: 1.08–2.31) were factors significantly associated with WMSDs. Conclusion WMSDs among nurses in Ethiopia are considerably high. The finding of our study may warrant attention in workplace risk management such as supportive management and ergonomic training and education, especially for female nurses and those with work experience (≥ 5 years). However, job stress and prolonged standing factors should be interpreted cautiously due to the substantial variability of covariates observed across studies.